Analysis of rainfall trends and dry periods on a pluviometric gradient representative of Mediterranean climate in the Duero Basin, Spain - Ceballos, Antonio; Martı́nez-Fernández, José; Luengo-Ugidos, Miguel Ángel (Journal of Arid Environments, 2004)
The present work studies the trends in rainfall and the behaviour of dry spells along a pluviometric gradient representative of the conditions of the Mediterranean region. The region is characterized by a marked water deﬁcit in the summer, a pronounced irregularity in its rainfall regime, and a noteworthy frequency of dry spells or periods without appreciable rainfall. The results obtained conﬁrm the general previsions of the IPCC, with a predominance of dry years over wet ones and a negative rainfall trend in the central sector. An increase in intra-annual variability in rainfall, and a very pronounced occurrence of dry periods independent of the total annual rainfall, are also seen. These circumstances will potentially increase the vulnerability of several Mediterranean ecosystems located along the gradient that are currently subject to considerable pressure from human activities; this will increase the environmental problems of these zones (agro-forestry–grazing productivity, soil degradation, recharge of aquifers, forest ﬁres, runoff models, biological diversity and composition, etc.).
Keywords: dry spells; duero basin; Mediterranean ecosystems; rainfall gradient; rainfall variability

Analysis of rainfall trends and dry periods on a pluviometric gradient representative of Mediterranean climate in the Duero Basin, Spain - Ceballos, Antonio; Martı́nez-Fernández, José; Luengo-Ugidos, Miguel Ángel (Journal of Arid Environments, 2004)
The present work studies the trends in rainfall and the behaviour of dry spells along a pluviometric gradient representative of the conditions of the Mediterranean region. The region is characterized by a marked water deﬁcit in the summer, a pronounced irregularity in its rainfall regime, and a noteworthy frequency of dry spells or periods without appreciable rainfall. The results obtained conﬁrm the general previsions of the IPCC, with a predominance of dry years over wet ones and a negative rainfall trend in the central sector. An increase in intra-annual variability in rainfall, and a very pronounced occurrence of dry periods independent of the total annual rainfall, are also seen. These circumstances will potentially increase the vulnerability of several Mediterranean ecosystems located along the gradient that are currently subject to considerable pressure from human activities; this will increase the environmental problems of these zones (agro-forestry–grazing productivity, soil degradation, recharge of aquifers, forest ﬁres, runoff models, biological diversity and composition, etc.).
Keywords: dry spells; duero basin; Mediterranean ecosystems; rainfall gradient; rainfall variability